Nilai-Nilai Pendidikan Dalam Surah Lukman - Garancang, Sabaruddin (Jurnal Studi Al-Qur'an, 2009)
Alquran as a guidance has many aspects encouraging the quality of human resources, like educational aspect. Alquran gives an advice about the education in order to make that human being has a good and strong mentality. The educational value of Luqman al-Hakim described in surah Luqman [31] contains several aspects: Firstly, the belief or faith building aspect as a basic principle in Islam. The doctrine of Luqman that is reflected clearly in the surah Luqman [31]: 13; Secondly, ritual aspect as described in the verse 17 which leads his son persuasively to pray as a form of the faith; Thirdly, character building aspect which is described in the verses 14, 15, and 18. Luqman stimulates his son to respect his parents and to treat his personal apparent nicely in daily life; Fourthly, personal and social building aspect that takes a long time, from the fetus till 21 years old. This case can be understood from verse 16 in surah Luqman.